FORMULASI DAN UJI FISIK GEL EKSTRAK DAUN SALAM (Syzygium poliyantum (Wight) Walp) DENGAN GELLING AGENT HPMC (Hydroxypropyl Methylcellulose) - Yunita Dian Permatasari; Dwi Islamiyati; Umi Nafisah (Jurnal Farmasindo, 2020)
Nowdays, medical plants have been widely used for overcome health problem. One of the nutritious plants is Bay Plant (Syzygium poliyantum (Wight) Walp) which contains flavonoid active compound, saponin which contains flavonoid compounds, saponins, which are used as antibacterial. This study aims to determine the gel formulation and evaluation as well as the effect of differences in the concentration of HPMC (Hydroxypropyl Methylcellulose) on the physical properties og the gel. In this study used variations in the HPMC concentrations of 4%, 5% and 6% with bay leaf extract concentrations of 5%. Bay leaves extracted by maceration for 7 days, then will be remacerated for 2 days to find the compouds that were still left with 70% ethanol solvent. Gel evaluation includes organoleptic, spread power, adhesion, pH, homogeneity, and protection. The evaluation result showed that at a concentration of HPMC 4%, 5% and 6% each had a distinctive odor of bay leaf extract and brown colored in an organoleptic test, produced homogeneus preparations, had a pH value of 6,16; 5,82; and 5,73; spread power 6,2 cm; 5,8 cm; and 5,1 cm; Stickness 5,75 sec; 7,46 sec; and 9.35 sec; and protective power 6,57 sec; 6,87 sec; 6.89 sec. The results of pH test, spreadability, and stickness using Kruskal Wallis showed an Asymp.Sig < 0.05% that is 0.000, which indicates that there are significant difference between the concentration of HPMC with ph test, spreadability and stickness. The result of protective power test showed an Asymp.Sig > 0.05 that is 0.497 and there is no significant difference between the concentration of HPMC with the protective power. The result of testing all three formulas meet the requirements except for protective power.